1998 Nagano Winter Olympic Games short-track speed skating project description
Information on the 1998 Nagano Winter Olympic Games short-track speed skating project - 1. Overview (background, purpose, events, project period, venues, sponsors) 2. Project team (names and institutes of the persones involved) 3. Experiment (analysis type, control object, recording equipment, location of the cameras). - no results until december 6th, 1999 -